Historiography of Russian-Chinese relations in the XVII century (Journal of Oriental Studies, 2016)
This article provides a historiographical analysis of literature Russian-Chinese relations in the XVII century. Relations between Russia and China has been and remains an important factor in world history, international relations and civilizational ties. At the turn of XVII - XVIII centuries. It began a political, trade-economic and cultural cooperation between Russia and China. Russian-Chinese relations for several centuries offers different  characteristics and follows the internal logic of the development of relations between states.
Keywords: Russia; China; the Russian-Chinese relations; historiography; economic relations